Ammonia borane-based reactive mixture for trapping and converting carbon dioxide - CASTILLA-MARTINEZ, Carlos A.; COSKUNER FILIZ, Bilge; PETIT, Eddy; KANTURK FIGEN, Aysel; DEMIRCI, Umit B. (HIGHER EDUCATION PRESS, 2022)
Ammonia borane (NH3BH3) is a reducing agent, able to trap and convert carbon dioxide. In the present work, we used a reactive solid consisting of a mixture of 90 wt.% of NH3BH3 and 10 wt.% of palladium chloride, because the mixture reacts in a fast and exothermic way while releasing H-2 and generating catalytic Pd-0. We took advantage of such reactivity to trap and convert CO2 (7 bar), knowing besides that Pd-0 is a CO2 hydrogenation catalyst. The operation (i.e. stage 1) was effective: BNH polymers, and B-O, C=O, C-O, and C-H bonds (like in BOCH3 and BOOCH groups) were identified. We then (in stage 2) pyrolyzed the as-obtained solid at 1250 degrees C and washed it with water. In doing so, we isolated cyclotriboric acid H3B3O6 (stemming from B2O3 formed at 1250 degrees C), hexagonal boron nitride, and graphitic carbon. In conclusion, the stage 1 showed that CO2 can be 'trapped' and converted, resulting in the formation of BOCH3 and BOOCH groups (possible sources of methanol and formic acid), and the stage 2 showed that CO2 transforms into graphitic carbon.
Keywords: ammonia borane; boron nitride; boron oxide; carbon dioxide; graphitic carbon; CO2 REDUCTION; HYDROGEN; BOROHYDRIDE; RELEASE; NANOPARTICLES; TEMPERATURE; CHLORIDE; SODIUM; ACID; B-11; Materials Science